E-SCAVENGER: UI/UX DESIGN OF AN ANDROID-BASED SCAVENGER APPLICATION USING HUMAN-CENTERED DESIGN METHODOLOGY IN PALOPO CITY - Ardiansyah Saputra; Nirsal, Nirsal (Informatika, Universitas Jenderal Soedirman, 2024)
Efficient waste management and active community participation are key to keeping cities clean and reducing negative impacts on health and the environment.